SLEEP QUALITY AND COLLEGE STUDENT BLOOD PRESSURE IN WIDYA MANDALA CATHOLIC UNIVERSITY SURABAYA - Cindy Clareta; Pauline Meryana; Endang Isbandiati (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: Changes in sleep patterns that occur in college student due to the alteration of direct learning system, after 2 years of long distance education caused by the COVID-19 pandemic affect the adaptation process of circadian rhythm. Poor sleep quality that happened because of sleep changes patterns is liable to increased the mortality risk due to the escalation incidence of chronic diseases, cardiovascular disorder such as hypertension for the example. The prevalences of adolescent (population > 18 years) with hypertension in Indonesia is quite high at 34.11%.Objective: The study aims to learn the relationship between sleep quality and college student blood pressure in Widya Mandala Catholic University Surabaya.Method: The study used a cross-sectional approach in UKWMS faculty of medicine student. The method that used in this research, was simple random sampling and obtained 80 respondents. The data was carried out by sharing questionnaires in google forms that contains data related to sleep quality, after that we measured the blood pressure.Result: in this study, it was found out that the majority was the respondents who had a good sleep quality and normal blood pressure with a total of 37 students (77.1%), good sleep quality and abnormal blood pressure with a total of 11 students (22.9%), bad sleep quality and normal blood pressure with a total of 13 students (34.2%), bad sleep quality and abnormal blood pressure with a total of 25 students (65.8%) the result were p=0.00 (p<0.05), so it can be concluded that there was a relationship between sleep quality and blood pressure in Widya Mandala college student Surabaya.